METODE BERCERITA BERBASIS MEDIA FLIP CHART TERHADAP KEMAMPUAN BERBICARA SISWA TUNARUNGU - M FIRDAUSIY, R (Jurnal Pendidikan Khusus, 2016)
ABSTRACT The purpose of this research was to observe whether there was influence of telling story method based flip chart media toward speaking ability to hearing impairment students of class II in SLB BC Karya Bhakti Surabaya or not. The result which would be reached was the speaking ability of hearing impairment students. This research used pre experiment kind. The time applied was 8 times meeting with 6 times treatment. The research design used was one group pre test – post test design with the subject 6 students. The data collection method was done by observation and test. The data analysis used was statistic non parametric with sign test. From the research result which was then analyzed using sign test formula, it was obtained Z counted (ZH) 2,05 whereas Z table Zt) in 5% significant for one side test was 1,64 and two sides test was 1% (Zt = 1%) so Ho was refused (1,64 < 2,05 > 2,04). Based on the explanation above, it could be concluded that there was influence of telling story method based flip chart media toward speaking ability to hearing impairment students of class II in SLB BC Karya Bhakti Surabaya.   Keywords: Telling story method, flip chart media, speaking ability